ANALISIS PENGARUH INFLASI DAN SUKU BUNGA SERTIFIKAT BANK INDONESIA (SBI) TERHADAP INDEKS SAHAM LQ45 DI BURSA EFEK INDONESIA (BEI) - Dheo Rimbano (Politeknik Negeri Sriwijaya, 2015)
The purpose of this study was to determine whether the inflation effect on stock index LQ45 in Indonesia Stock Exchange (BEI). to find out if the SBI interest rate affects the index LQ45 in Indonesia Stock Exchange (BEI) and to find out if inflation and interest rates affect the SBI share index LQ45 in Indonesia Stock Exchange (IDX) To test the hypothesis the researchers used F test and t test. Test results obtained figures F 32.292 with sig. namely 0,000, as the value of F count> F table (32.292> 3.159) then H0 is rejected, meaning that Inflation and Interest Rates significant effect on stock index LQ45 in Indonesia Stock Exchange (BEI). Results of t test variable inflation figures obtained .968 with sig. ie 0.337, because the value of t <t table (0.968 <2.002) then H0 accepted, it means that inflation is not a significant effect on stock index LQ45 in Indonesia Stock Exchange (BEI). Results of t test variable interest rates SBI -7.697 figures obtained with sig. namely 0,000, since the value t count> t table (-7.697> -2.002) then H0 is rejected, meaning that the SBI interest rate significantly influence the LQ45 index in the Indonesia Stock Exchange (BEI).